Calculation of Electric Field Characteristics of Insulator Under Sandstorm Condition - Zhao Shanpeng; Zhang Youpeng; Chen Zhidong; Dong Haiyan (Institute of Advanced Engineering and Science, 2014)
Sandstorm has influence on the the electrical properties of outdoor insulator, and the analysis of the electric field characteristics of insulator under sandstorm condition is very important. The electrostatic field finite element method (FEM) is used to calculate the electric field distribution along long rod insulator under sandstorm condition with FEM software after calculating the one under clean condition. The results of calculation show that the sand deposition decreases the electric field strength of insulator covered with sand, and increases the field strength of the corresponding shed key points. The electric field strength of the non-sand region will increase, when the non-sand region appears in sand layer on insulator. Suspended sand particles in the ambient air can distort the electric field distribution along insulator, and which is significantly affected by the size, the quantity, the charge-to-mass ratio and the charge polarity of sand particles. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3902